Analysis of the current state of the loan portfolio of commercial banks - Rakhimzhanova, K.; Zhorabaуeva, G.; Aliуeva, B. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2022)
One of the main factors hindering the stability of the banking sector is problem loans. These problem loans reduce the liquidity of banks, as well as the development of the economy as a whole. Problem loans are loans with a low probability of non-repayment or repayment of debt. Therefore, after issuing a loan, the bank must take measures to ensure that there are no loan expenses. The management of problem loans is one of the most important aspects of banking practice. The article is devoted to ensuring the optimization of the quality of the loan portfolio of Kazakhstani banks and their structure. The main problem is the high proportion of problem loans in the structure of the loan portfolio of some domestic banks. Analysis of the loan portfolio of banks in the top 5 STBs with the largest volume of non-performing loans. Analysis of the structure of the loan portfolio of banks in the top 5 STBs with the highest concentration of non-performing loans. There are also considered the main directions of the work of the Problem Loans Fund.